Improving Toddlers’ Appetite through Tuina Massage and Feeding Rules: A Preventive Approach to Stunting - Tiwery, Indah Benita; Leutualy, Vanny; Palapessy, Vriyana; Akely, Wuilel Marok (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Stunting remains a major public health concern in Indonesia due to its long-term implications for child development and national productivity. Among the contributing factors are inappropriate dietary patterns and poor parental responses to appetite loss among toddlers. This study examined the effects of tuina massage using virgin coconut oil (VCO) combined with structured feeding rules on the appetite of stunted toddlers. A quasi-experimental design with a pretest–posttest control group was conducted in Laha Village, involving 40 stunted toddlers aged 12–36 months. Participants were assigned to either an intervention or control group through total sampling. The intervention consisted of six consecutive days of tuina massage using VCO and the implementation of scheduled feeding rules. Appetite levels were assessed using a validated questionnaire administered before and after the intervention. Data were analyzed using Shapiro–Wilk for normality, followed by Wilcoxon, paired t-tests, and Mann–Whitney U tests. Results showed a statistically significant improvement in appetite among children in the intervention group (p < 0.001), whereas no changes were observed in the control group. These findings indicate that the integrated intervention effectively enhances appetite in stunted toddlers and offers a promising, low-cost, and non-pharmacological strategy for addressing stunting in low-resource settings. The combination of physiological stimulation through massage and behavioral regulation through structured feeding rules provides a holistic approach to improving early childhood nutrition. Further studies with longer duration and broader geographic scope are recommended to evaluate long-term impacts and scalability within public health programs.